Perception Study On Ergonomics Practices In Malaysian Quarry And Mining Industry - Norhidayah, M. S.; Ahmad Rasdan, Ismail; Muhamad Arifpin, Mansor (2015)
Ergonomics can be viewed as an approach to reduce injury and illness rates to improve the overall working conditions for employees by addressing risk factor exposure that may occur during manual tasks. The objective of this research was to analyze ergonomics risk factors by associating the perception of employer and employees towards their workplace condition in quarry and mining industry. A Questionnaire on Ergonomics Risk Assessment was used to determine the comparison level awareness and perception analysis among quarry and mining industry in